2020
DOI: 10.1016/j.molp.2019.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Network Promotes Anthocyanin Biosynthesis in Tomato Flesh

Abstract: Dietary anthocyanins are important health-promoting antioxidants that make a major contribution to the quality of fruits. It is intriguing that most tomato cultivars do not produce anthocyanins in fruit. However, the purple tomato variety Indigo Rose, which has the dominant Aft locus combined with the recessive atv locus from wild tomato species, exhibits light-dependent anthocyanin accumulation in the fruit skin.Here, we report that Aft encodes a functional anthocyanin activator named SlAN2-like, while atv en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
155
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 51 publications
4
155
0
Order By: Relevance
“…Dietary anthocyanins, which are important health-promoting antioxidants, make major contribution to the quality of fruits or leaves. Furthermore, dietary anthocyanin accumulation is also recognized as a visible biomarker of plants that have suffered from environmental stresses in many studies (Xie Y. et al, 2016;Zheng et al, 2019;Sun et al, 2020). Anthocyanin biosynthesis and regulation pathway has been well studied in Cruciferae plants including Arabidopsis, Brassica rapa, Brassica oleracea, Brassica napus, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary anthocyanins, which are important health-promoting antioxidants, make major contribution to the quality of fruits or leaves. Furthermore, dietary anthocyanin accumulation is also recognized as a visible biomarker of plants that have suffered from environmental stresses in many studies (Xie Y. et al, 2016;Zheng et al, 2019;Sun et al, 2020). Anthocyanin biosynthesis and regulation pathway has been well studied in Cruciferae plants including Arabidopsis, Brassica rapa, Brassica oleracea, Brassica napus, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Chilling treatment as an effective method to promote dormancy release had been veri ed in many species including tree peony [3][4][5][41][42]. Transcriptomics, proteomics and microRNAs analysis had been performed to investigated the complex mechanism of chilling induced dormancy release in tree peony, which revealed the roles of GA and carbohydrate metabolism [7,13,27].…”
Section: Discussionmentioning
confidence: 99%
“…The pathway of avonoid biosynthesis was affected by biotic and abiotic factors (e.g., pathogen infections, temperature, drought, plant hormones) [30]. Moreover, recent reports had shown that avonoids were involved in plant stress response [31], pollen development [32], color formation [33], etc. However, it remained unknown whether avonoids participate in the process of dormancy release.…”
Section: Introductionmentioning
confidence: 99%